2018
DOI: 10.1002/slct.201701446
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Electrocatalysts for Hydrogen Evolution Reaction Using Flexible Electrodes Made up of Chemically Modified Polyester Films

Abstract: In this work we propose a simple methodology to fabricate monometallic nickel [Ni] and bimetallic silver‐nickel [Ag/Ni] deposited flexible, self‐supported electrodes using polyester (commonly used as overhead projector [OHP]) films. Monometallic Ni is deposited onto chemically modified OHP sheets using a simple electroless deposition process. Similarly bimetallic Ag/Ni coating is carried out by employing galvanic replacement reaction (GRR) of silver onto Ni coated polyester films. Structure, morphology, compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Furthermore, the surfactants such as sodium dodecyl sulfate (SDS), t‐octyl phenoxy poly ethoxy ethanol (Triton X‐100), and cetyl trimethyl ammonium bromide (CTAB) increased the current density of HER, with SDS providing the highest HER activity of Pd–Cu bimetallic NPs. Thota et al reported that the HER activity of the bimetallic Ag/Ni heterostructures deposited on a flexible polyester film (overhead projector, OHP) could be optimized by varying the GRR time, resulting in different surface morphologies and varied ratios of silver and nickel within the deposit 101 . Compared to the monometallic Ni/OHP and Ag/OHP electrodes, the Ag/Ni/OHP electrodes prepared through 5 min of GRR exhibited the lowest onset potential of −75 mV.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the surfactants such as sodium dodecyl sulfate (SDS), t‐octyl phenoxy poly ethoxy ethanol (Triton X‐100), and cetyl trimethyl ammonium bromide (CTAB) increased the current density of HER, with SDS providing the highest HER activity of Pd–Cu bimetallic NPs. Thota et al reported that the HER activity of the bimetallic Ag/Ni heterostructures deposited on a flexible polyester film (overhead projector, OHP) could be optimized by varying the GRR time, resulting in different surface morphologies and varied ratios of silver and nickel within the deposit 101 . Compared to the monometallic Ni/OHP and Ag/OHP electrodes, the Ag/Ni/OHP electrodes prepared through 5 min of GRR exhibited the lowest onset potential of −75 mV.…”
Section: Applicationsmentioning
confidence: 99%
“…Thota et al reported that the HER activity of the bimetallic Ag/Ni heterostructures deposited on a flexible polyester film (overhead projector, OHP) could be optimized by varying the GRR time, resulting in different surface morphologies and varied ratios of silver and nickel within the deposit. 101 the electrodeposited Co(OH) 2 was increased, the corresponding sample exhibited slower kinetics and increased charge transfer resistance.…”
Section: Hydrogen Evolution Reaction (Her)mentioning
confidence: 99%